Different strokes for different folks: Entrepreneurs' job satisfaction and the intersection of gender and migration background - Teita Bijedić; Alan T. Piper (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Migrant enterprises comprise about 10% of all enterprises in Germany and are therefore a crucial part of the German economy and its entrepreneurial ecosystems. Relatedly, migrant entrepreneurship is a highly recognized topic within political discussions as well as within entrepreneurship research. While there is already an impressive body of work regarding the nature and quality of migrant enterprises, many questions regarding the personal motives and satisfaction of migrant entrepreneurs still remain unanswered (particularly with reference to gender and generation of migration). Using the German Socio-Economic Panel dataset, we close this research gap by investigating the job satisfaction of migrant entrepreneurs in Germany compared with native entrepreneurs, and also with conventionally employed migrants and natives. First generation migrants show, in general, less job satisfaction than the native population. Second generation male migrant entrepreneurs' show less job satisfaction, however this association is reversed for females: second generation female migrant entrepreneurs are more satisfied with their self-employment than their native counterparts. These differing results lead to differing implications for policy makers who wish to create and develop entrepreneurial and labour market support for different target groups.
Keywords: L26; J15; J16; J28; 330; migrant entrepreneurship; family firms; job satisfaction; intersectionality